Cloud cognitive authenticator (CCA): a public cloud computing authentication mechanism - Jivanadham, L. B. (2013)
The long awaited Cloud computing concept is a reality now due to the advancement and transformation of computer generations. However, the implementation of this concept as a technology is still at infancy stage due to several issues such as policy, standards, users, security, etc. This paper features the basic concepts of cloud computing, security issues and proposes an integrated authentication mechanism called the Cloud Cognitive Authenticator (CCA). CCA is an API proposed for the cloud environment integrating bio-signals, one round Zero Knowledge Protocol (ZKP) for authentication and Rijndael algorithm in Advance Encryption Standard (AES). CCA is proposed to enhance the security in public cloud through four procedures providing two levels of authentication as well as encrypting/decrypting the user id. The novelty of CCA is that it uses Electro Dermal Responses (EDR) for the first level authentication. Furthermore, the proposed encryption in CCA provides concrete cryptography. Finally, this paper concludes with the future direction of this study.